2015
DOI: 10.1016/j.rboe.2015.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic study on the anatomical characteristics of the proximal femur in Brazilian adults

Abstract: ObjectiveTo ascertain the geometry of the femur in the Brazilian population by means of a radiographic study and to correlate the values with regard to sex and right/left side.MethodsFive hundred anteroposterior radiographs of the pelvis of skeletally mature patients (250 of each sex) who did not present any osteoarthrosis, fractures or tumoral or infectious lesions were analyzed. The length and width of the femoral neck, length of the femoral axis, neck-shaft angle and femoral offset were measured.ResultsThe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 21 publications
2
5
4
Order By: Relevance
“…On the opposite side, the VDH and TDH in adult male and female Caucasians and Mongoloid [14], South Indians [15] and Brazilians [16] were lower than these of the present study. he South Indian populations are vegetarians, so they lack the protein in their food habit and this may be the reason for their low dimensions [8].…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…On the opposite side, the VDH and TDH in adult male and female Caucasians and Mongoloid [14], South Indians [15] and Brazilians [16] were lower than these of the present study. he South Indian populations are vegetarians, so they lack the protein in their food habit and this may be the reason for their low dimensions [8].…”
Section: Discussioncontrasting
confidence: 94%
“…he TDN was 7% and 8% lower in females as compared to theses of males on the right and let sides respectively. In support of the current work, many authors reported similar side diferences of theses parameters among populations from India and Brazil [1,15,16]. he mean of all these studies, were lower than theses of the present study.…”
Section: Discussionsupporting
confidence: 88%
“…Males were noted to have a larger femoral head diameter and greater offset as has been shown in previous populations (Table ) …”
Section: Resultssupporting
confidence: 58%
“…1 ). For evaluating femoral neck length, the articulo-trochanteric distance (ATD) [ 23 ] and femoral neck length ratio [ 24 ] was measured and calculated, respectively. For evaluating acetabular morphology and subluxation, Sharp angle [ 25 ], acetabular roof angle [ 26 ], lateral center-edge angle (LCEA) [ 27 ], medial joint space (MJS) width ratio [ 28 ], and center-head distance discrepancy (CHDD) [ 29 ] were measured.…”
Section: Methodsmentioning
confidence: 99%